East Timor's transition to independence: Building up an economy from scratch - Rainer Thiele (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2000)
After the extensive destruction caused by the violence that followed the vote for independence on August 30th, 1999, the reconstruction of East Timor's infrastructure inevitably was the top priority. Supported by massive aid inflows, achievements in this area have been quite remarkable. As a result, East Timor's production capacity is likely to return to pre-crisis levels within a few years. The much more difficult task is to initiate and then sustain a long-run development process. This requires a whole bundle of measures of which only a part has been introduced up to now. At the macroeconomic level, three policy areas figure most prominently. First, to ensure a certain degree of macroeconomic stability as a prerequisite for growth, it is recommended to implement a combination of a Currency Board regime for the exchange rate and a sound fiscal policy based on a broad domestic revenue base. Second, permanent growth can only be achieved via the accumulation of physical and human capital. Secure property rights and a transparent investment code are among the essential conditions for physical capital formation. Human capital formation can be fostered by reallocating public resources towards basic services, which were seriously neglected under Indonesian rule. Third, a country like East Timor with its very small domestic market and its limited technical knowledge can reap large benefits from adopting an open trade and foreign investment regime. From a sectoral perspective, agriculture will remain the backbone of the economy in the foreseeable future. Incentives that lead to a more dynamic development of this sector are thus of particular importance, not only for growth but also for poverty alleviation as the vast majority of poor people live in rural areas. Such incentives include a market-oriented pricing policy, a stable and competitive exchange rate, access to credit, a basic rural infrastructure, and the provision of adequate research and extension facilities. A development strategy based on agriculture alone would, however, leave the economy vulnerable to shocks. Only a diversification of production will open the way to more robust growth. One significant step in this direction could be the exploitation of existing oil fields. If future oil revenues live up to expectations, the main policy challenge will be to avoid an overvaluation of the domestic currency (Dutch Disease). In the medium run, the establishment of labor-intensive industries could be another step towards a more diversified economy. Whether this option can be realized will depend to a large extent on East Timor's ability to import capital and know-how via foreign direct investment. Overall, if political stability prevails, the outlook for sustained progress seems better than in many other low-income countries, where the international community is less consistently engaged and where much stronger vested interests block reform efforts. At the moment, the most significant danger for long-term development in East Timor arises from the uncertainty of land and property rights, which is likely to hamper investment and agricultural development. Moreover, it has to be kept in mind that various important measures, such as investments in education, will take considerable time to materialize fully.
Keywords: 330; Volkswirtschaft; Nationale Selbstbestimmung; Entwicklungspolitik; Kriegsschaden